Deutsche Banken auf dem Weg in die zweite Globalisierung = German banks on the way to the second globalization - Sattler, Friederike 1964-; Ziegler, Dieter 1956- (De Gruyter Oldenbourg, 2023)
Abstract: This article introduces the problematic situation of the great German banks and some non-German banks during the so-called second globalization since the 1970s. It formulates the questions that should be answered in the following contributions, each for a particular bank or group of banks. The most important overarching questions are firstly, to what extent banks were the driving force in the interconnectedness of cross-border money and capital flows and, secondly, to what extent they acted as triggers of the severe financial and/or sovereign debt crises during the last half century.
Keywords: Geschichte 1949-2000; Globalisierung; Bank; Deutschland; Second Globalisation; Petrodollar recycling; debt crises; Zweite Globalisierung; Schuldenkrisen; Aufsatzsammlung